2013
DOI: 10.1515/jcim-2012-0006
|View full text |Cite
|
Sign up to set email alerts
|

Laser acupuncture in treatment of childhood bronchial asthma

Abstract: low-intensity laser acupuncture can be safe and effective treatment in asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These studies demonstrate the efficacy of laser in acute inflammatory pulmonary diseases [4, 5], chronic fibrotic pulmonary diseases [6, 7], and experimental asthma using ovalbumin [810]. Some studies have used LLLT in the clinical area and as a result have observed improvement in spirometric parameters, reduction of exhaled nitric oxide concentration, improved control of asthma exacerbation, and consequent reduction in drug use [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate the efficacy of laser in acute inflammatory pulmonary diseases [4, 5], chronic fibrotic pulmonary diseases [6, 7], and experimental asthma using ovalbumin [810]. Some studies have used LLLT in the clinical area and as a result have observed improvement in spirometric parameters, reduction of exhaled nitric oxide concentration, improved control of asthma exacerbation, and consequent reduction in drug use [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 50 asthmatic children randomly selected from a clinic were evaluated 1 month after receiving 10 laser acupuncture sessions. Statistically significant improvement (P < 0.001) was seen in nocturnal symptoms, exercise tolerance, FEV1, and FVC, as well as asthma control questionnaire, and the majority of the patients became well controlled on decreased inhaled steroids and short-acting b2-agonist [42]. A longer follow-up study would be of interest to determine the length of treatment needed to sustain these results.…”
Section: Acupuncturementioning
confidence: 98%
“…In Egypt, laser acupuncture was performed 3 sessions per week in 50 children followed for asthma and it was stated that an improvement in respiratory function tests were observed, beta-mimetic drugs were discontinued, and the dose of inhaled corticosteroids was reduced after the 1-month treatment period [50].…”
Section: Allergic System Diseasesmentioning
confidence: 99%